Cell walls as a stage for intercellular communication regulating shoot meristem development - Tameshige, Toshiaki; Hirakawa, Yuki; Torii, Keiko U.; Uchida, Naoyuki (Frontiers in Plant Science, 2015)
Aboveground organs of plants are ultimately derived/generated from the shoot apical meristem (SAM), which is the proliferative tissue located at the apex of the stem. The SAM contains a population of stem cells that provide new cells for organ/tissue formation. The SAM is composed of distinct cell layers and zones with different properties. Primordia of lateral organs develop at the periphery of the SAM. The shoot apex is a dynamic and complex tissue, and as such intercellular communications among cells, layers and zones play significant roles in the coordination of cell proliferation, growth and differentiation to achieve elaborate morphogenesis. Recent findings have highlighted the importance of a number of singling molecules acting in the cell wall space for the intercellular communication, including classic phytohormones and secretory peptides. Moreover, accumulating evidences reveal that cell wall properties and their modifying enzymes modulate hormone actions. In this review, we overview how behaviors of singling molecules and changes of cell wall properties are integrated for the shoot meristem regulation.